Decomposition of DNAN-based explosive (296 mg) in a Laboratory-Scale open setup - Galante, Erick; Gill, Philip; Temple, Tracey (Cranfield University, 2018)
Thermo decomposition of 296mg of DNAN-based Insensitive high explosive heated from beneath, in an open setup, on a metal tray within a laboratory.
Keywords: 'decomposition'; 'dnan'; 'laboratory-scale burning'; 'Chemical Characterisation of Materials'; 'Chemical Thermodynamics and Energetics'; 'Environmental Chemistry'